Pengembangan Teknik Modeling Simbolik untuk Meningkatkan Perilaku Menjaga Kelestarian Hutan Kalimantan - Mohammad Fatchurahman; Karyanti Karyanti (Anterior Jurnal, 2019)
The objectives of this study are (1) To find out the implementation of symbolic modeling techniques and an overview of the behavior of preserving forests by adolescents. (2) Compilation of symbolic modeling techniques used to improve forest preservation behavior. The research method used is Research and Development (R & D). Research and development or development research are one of the studies which at the end of the research can be found a new model. Data analysis is done in quantitative and qualitative ways. The results of the model development that have been carried out by the researcher include a model that contains (1) Rational, (2) Objectives, (3) Assumptions, (4) Target interventions, (5) Model components, (6) Model steps, ( 7) Material, (8) Means, (9) Evaluation and indicators of success. The arranged model is tested to determine the effectiveness of the model that has been arranged. The results of the trial show that symbolic modeling techniques are effective in increasing forest preservation behavior. That means there is an increase in understanding of forest preservation behavior. Therefore, it can be concluded that symbolic modeling techniques are effective in increasing forest preservation behavior.